Adapting to reality - Kákai, László (Central European Public Administration Review, 2026)
Purpose: The literature on centralisation and decentralisation pays little attention to how the structure itself influences voters’ and, ultimately, consumers’ access to public services and, through this, their attitudes. Do those who consider local governments to be essential providers of public services regard local autonomy as more important than those who expect the state to ensure the quality of services? Hungary is an excellent case for the empirical examination of this question, as the fundamentally decentralised structure established in 1990 has shifted increasingly towards centralisation in recent years. This allows us to assess how the ongoing centralisation process, implemented in several waves since 2010, shapes citizens’ attitudes and expectations towards local governments and public services. Methodology: To examine this, we use a database collected through two large-scale questionnaire surveys conducted five years apart. The data from the two population surveys (first wave in 2018, second wave in 2023) are comparable, as the same questions were repeated in both surveys. While the 2018 data collection was based on personal interviews with 1,500 respondents, the 2023 data collection was based on an online sample of 1,800 respondents, with both data collections representative in terms of municipality size, educational level, gender, and age group. The survey therefore examines the attitudes and changing expectations of the population towards local governments and public services in a system that has become increasingly centralised since 2010. I seek answers to the central question of how the government’s reduction of local government autonomy affects voters’ trust in local governments and public services. Findings: The survey results highlighted several disadvantages of the centralisation of public services, mainly resulting from the neglect of local needs. The results show that people prefer accessibility and proximity to service providers, especially when they do not perceive significant improvements in quality or accessibility. The distribution of opinions suggests that it is no exaggeration to say that local governments, by their very existence, represent a source of value for people in a certain sense. At the same time, the responses clearly show the effects of strong government centralisation, as people, especially in small towns and villages, expect certain services to be provided by the state and do not see a problem with the fact that some functions were previously the responsibility of local governments. Academic contribution to the field: The study uses empirical data processing and quantitative evaluation, thereby creating opportunities for further methodological development in research on this topic. Its methods and results differ from the mainstream of traditional research on centralisation and decentralisation, which is generally based on qualitative evaluation. The study primarily applies policy feedback theory to examine the long-term effects of centralisation on citizens’ attitudes. It reveals a “pragmatic duality” in public opinion, whereby citizens’ expectations shift towards the central state despite their normative support for local autonomy. Research implications/limitation: The results clearly show that respondents partly follow the government’s centralisation intentions; that is, the choice between local self-government and centralisation is less important to them. Although they consider the existence of local government important, they do not primarily associate it with the number or quality of public services, but rather with decision-making autonomy, so that certain decisions can be made at the local government level. Originality/value: The study is also original in that it presents and analyses changes in access to services and in relations between central government and local authorities. Using empirical and comparable databases, it shows the extent and impact of change on local consumers, thereby enriching the debate on centralisation and decentralisation and exploring possible directions for the future.
Keywords: autonomy; avtonomija; centralisation; centralizacija; decentralisation; decentralizacija; Hungary; javne storitve; local government; lokalna samouprava; Madžarska; public services